PENGARUH PEMBERIAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR PASSING BAWAH BOLAVOLI (STUDI PADA SISWA KELAS VII SMP NEGERI 1 YOSOWILANGUN LUMAJANG) - PAMBAYUN, NINDYTA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Under pass is a such a difficult matery for junior high school especially for 7th graders. Many students are lack of this capability both in the game and in the practice. It needs an accurate learning process which is appropriate with student’s characteristics to apply under pass capability perfectly. One of the learning model which can be used is TGT type. This learning model focuses on team working aspect, where the students are divided on some small groups which are chosen randomly based on gender and skill. In this case, students are asked to work on the small groups to study material given through playing volleyball game on each group. The achievement is defined by all members, so it involves all students in the learning activity. The study aims to know: 1) the influence of giving TGT type cooperative learning model towards the student’s achievement of under pass volleyball learning. 2) the improving of student’s achievement of under pass volleyball. The subject of this study is the 7th graders. There are 35 students are taken as the samples. The research methodology is an abstract experimental research, with one group pre-test post-test design. The statistic method is descriptive and comparative quantitative statistic analize. The data is taken from under pass test. The under pass test used brumbach forearm pass wall-volley test. The conclusion of this study is: 1) there is a significant influence of giving  cooperative learning model TGT type towards the student’s achievement of under pass volleyball on 7th graders of State Junior High School 1 Yosowilangun Lumajang. The result is Wilcoxon test. Those are Zcount 5,159 > Ztabel 1,96 and Asymp Sig = 0,000 < 0,05.. 2) the giving of  cooperative learning model TGT type towards the student’s achievement of under pass volleyball on 7th graders of State Junior High School 1 Yosowilangun Lumajang gives the improvement of student’s achievement of under pass. It increases 18,06%. Keywords : Under Pass, Cooperative, TGT, Volleyball, Achievement.